Transmission of Knowledge and Islamic Religious Education in Early Childhood: Parents' Roles, Constraints, and Solutions - Muh Hidayatullah S; Hisban Thaha; Alauddin Alauddin (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This study aims to understand the role of parents in fostering early childhood Islamic education, describe the obstacles and find solutions. This research uses descriptive qualitative research with a sociological and psychological approach. This research involved eight parents of early childhood students. Data collection techniques are observation, interview, and documentation. The results showed that the role of parents in early childhood religious development is to provide examples, habituation, and advice to children, especially in prayer, reciting the Quran and practising daily prayers. Imbara Permai 1 Housing parents experience several obstacles in carrying out their role, namely using cell phones for too long and the laziness that sometimes comes to the child. The steps taken by parents to overcome this are limiting the duration of cellphone use, taking children for walks, and playing with children.